2022
DOI: 10.3390/jfb13040278
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Melittin as a Lytic Agent via Graphene Nanoparticles as Carriers to Breast Cancer Cells

Abstract: Melittin, as an agent to lyse biological membranes, may be a promising therapeutic agent in the treatment of cancer. However, because of its nonspecific actions, there is a need to use a delivery method. The conducted research determined whether carbon nanoparticles, such as graphene and graphene oxide, could be carriers for melittin to breast cancer cells. The studies included the analysis of intracellular pH, the potential of cell membranes, the type of cellular transport, and the expression of receptor prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 112 publications
1
5
0
Order By: Relevance
“…It is worth emphasizing that the effects of the studied complexes are the result of simultaneous exposure to the nanomaterial and M and their interaction as factors harmful to cancer cells. The use of GN and GO allows the liberation of M by the nanomaterial, which has been confirmed in previous studies [42], and the reduction of its spread outside the tumor when administered into the tumor. Oxidative stress can cause the production of cytokines, which in turn are used to communicate with other cells [77].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is worth emphasizing that the effects of the studied complexes are the result of simultaneous exposure to the nanomaterial and M and their interaction as factors harmful to cancer cells. The use of GN and GO allows the liberation of M by the nanomaterial, which has been confirmed in previous studies [42], and the reduction of its spread outside the tumor when administered into the tumor. Oxidative stress can cause the production of cytokines, which in turn are used to communicate with other cells [77].…”
Section: Discussionsupporting
confidence: 75%
“…The level of encapsulation of M with GN was 86% and with GO it was 78%, which is a suitable indicator for potential therapeutic agents. It has been proven that MGN is transported to MDA-MB-231 cells through caveolin-dependent endocytosis, while MGO is transported in multiple ways [42]. In addition, the use of carbon nanoparticles reduced the rate of cell death by necrosis to a greater extent compared to the reduction resulting from M alone [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melittin-DM1 significantly increased the survival rates of melanoma mice than those under DM1 management alone. Moreover, a series of studies ( 86 , 87 , 179 ) investigated several strategies, such as innocuous nonspecific toxicity and increased stability of melittin in anti-breast cancer therapy. Daniluk and colleagues showed that compared to melittin alone, using diamond, pristine graphene, graphene oxide and carbon nanoparticles as the carriers for melittin reduced the level of necrosis in MDA-MD-231 and MCF-7 cells ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity of melittin to malignant breast cancer cells has attracted much attention ( 85 ). The tumoricidal properties of melittin on breast cancer cells have been investigated ( 86 , 87 ). Melittin could impede primary tumor growth and inhibit the growth of the metastatic sentinel lymph node in breast cancer models in vitro and in vivo ( 88 ).…”
Section: Antitumor Potential Of Melittinmentioning
confidence: 99%